Young, poor, and sick: The public health threat of energy poverty for children in Ireland. (January 2021) - Mohan, Gretta
Abstract: Children, particularly those of preschool ages (below 3 years), spend the majority of time indoors in the family home. Home conditions can impact upon occupant's health, with energy poverty identified as a public health concern in Europe and internationally. Children growing up in energy poor homes may be especially vulnerable to health impacts, though the area is relatively understudied. This study addresses a gap in understanding, examining the effect of household energy poverty on the health of resident children using longitudinal data from two cohorts – an Infant Cohort (aged 9 months to 5 years) and a Child Cohort (aged 9 years to 17–18 years), growing up in Ireland. Panel logistic regression models adjust for a range of covariates including socioeconomic and household information as well as smoking in the household. For the Infant Cohort, household energy poverty was associated with a 1.41 times higher odds of child respiratory illness (p = 0.003; 95% Confidence Interval (CI) 1.12–1.77), and 1.47 times the odds of child wheezing (p < 0.001; 95% CI 1.25–1.74). The odds of a young child being rated as very healthy was lower (point estimate: 0.85, p = 0.011; 95% CI 0.75–0.96). For older children, the relationships were not statistically significant. The risk that energy poverty presents for the health of young children merits continued policy attention.